1981
DOI: 10.4315/0362-028x-44.6.414
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sodium Nitrite, Sodium Nitrate and DL, Alpha-Tocopherol on Properties of Irradiated Frankfurters

Abstract: Frankfurters were manufactured to contain certain combinations of curing ingredients (sodium nitrite, sodium nitrate and DL alpha-tocopherol). Some frankfurters were made to contain in the finished product 0% added moisture, others were made to contain 10% added moisture, some frankfurters were not irradiated (0-megarad), others were irradiated with either 0.8 or 3.2 megarads (Cobalt-60 radiation source). Use of DL, alpha-tocopherol (at a level of 206 ppm) was associated with greater processing shrinkage, more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…Shahidi et al (1991) reported that sodium nitrite has a strong antioxidant effect on cured meat products. However, when higher doses of radiation was applied (48 kGy), lipid oxidation in cured meat increased (Terrell et al, 1981). The higher levels of TBARS values in turkey breast rolls than otheres were consistent with Zhu et al (2004aZhu et al ( , 2004c findings: the highest TBARS values in turkey breast rolls were due to the quality of the starting materials, which already had relatively high level of TBARS values.…”
Section: Lipid Oxidation and Protein Oxidationsupporting
confidence: 87%
“…Shahidi et al (1991) reported that sodium nitrite has a strong antioxidant effect on cured meat products. However, when higher doses of radiation was applied (48 kGy), lipid oxidation in cured meat increased (Terrell et al, 1981). The higher levels of TBARS values in turkey breast rolls than otheres were consistent with Zhu et al (2004aZhu et al ( , 2004c findings: the highest TBARS values in turkey breast rolls were due to the quality of the starting materials, which already had relatively high level of TBARS values.…”
Section: Lipid Oxidation and Protein Oxidationsupporting
confidence: 87%
“…It therefore acts as a competitive inhibitor, preventing the degradation of food constituents (23). Addition of sorbates prior to irradiation has been reported to improve the sensory qualities of foods (23,(223)(224)(225)(226). Ascorbic acid also acts as a competitive inhibitor by reacting with *OH radicals and hydrated electrons (20).…”
Section: Use Of Additivesmentioning
confidence: 98%
“…Ascorbic acid also acts as a competitive inhibitor by reacting with *OH radicals and hydrated electrons (20). Nitrites or nitrates improve the color and palatability of irradiated frankfurters (226). Other chemicals -e.g., iodoacetamide, iodoacetic acid, captan, etc.-have been reported to radiosensitize the microorganism, thus reducing the dose required for their inhibition (227,228).…”
Section: Use Of Additivesmentioning
confidence: 99%
“…Irradiation and lactate‐based additives, particularly in combination with diacetate, are effective antimicrobials in ready‐to‐eat (RTE) processed meats (Papadopoulous and others 1991b; Eckert and others 1997; Maca and others 1997a; Sommers and Thayer 2000; Mbandi and Shelef 2001; Samelis and others 2002; Sommers and Fan 2003; Nunez and others 2004a). However, the use of either technology alone as a microbial intervention strategy can result in undesirable quality changes (Terrell and others 1981a, 1981b, 1982; Nunez and others 2004b). An intervention strategy that addresses both consumer safety concerns and quality issues is the use of multiple microbial hurdles, which uses compatible antimicrobial technologies together at lower usage levels to suppress pathogen growth while preserving desirable physiochemical and sensory properties.…”
Section: Introductionmentioning
confidence: 99%